2003
DOI: 10.1097/01.asn.0000088024.72216.2e
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Renal Failure Accelerates Atherogenesis in Apolipoprotein E–Deficient Mice

Abstract: Abstract. Cardiovascular mortality is 10 to 20 times increased in patients with chronic renal failure (CRF). Risk factors for atherosclerosis are abundant in patients with CRF. However, the pathogenesis of cardiovascular disease in CRF remains to be elucidated. The effect of CRF on the development of atherosclerosis in apolipoprotein E-deficient male mice was examined. Seven-week-old mice underwent 5/6 nephrectomy (CRF, n ϭ 28), unilateral nephrectomy (UNX, n ϭ 24), or no surgery (n ϭ 23). Twenty-two weeks lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

24
119
5
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(152 citation statements)
references
References 52 publications
24
119
5
4
Order By: Relevance
“…Thus both the morphologic and biochemical analyses in this study suggest that accelerated initiation and expansion of lesions rather than specific lesion composition is the key characteristic of early uremic atherosclerosis in apo-EϪ/Ϫ mice. This notion is in accordance with our former study, where we studied mice that had been uremic for 22 wk and had extensive aortic atherosclerosis with a mean total plaque area of 0.27 (8). In that study, we observed aortic lesions with extracellular lipids, lipid-filled macrophages, lymphocytes, and collagen-rich connective tissue, i.e.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Thus both the morphologic and biochemical analyses in this study suggest that accelerated initiation and expansion of lesions rather than specific lesion composition is the key characteristic of early uremic atherosclerosis in apo-EϪ/Ϫ mice. This notion is in accordance with our former study, where we studied mice that had been uremic for 22 wk and had extensive aortic atherosclerosis with a mean total plaque area of 0.27 (8). In that study, we observed aortic lesions with extracellular lipids, lipid-filled macrophages, lymphocytes, and collagen-rich connective tissue, i.e.…”
Section: Discussionsupporting
confidence: 92%
“…characteristics of more advanced classical atherosclerosis. Remarkably, aortic calcifications are virtually absent in uremic apo-EϪ/Ϫ mice (8,9), despite significantly elevated plasma concentrations of calcium and phosphate (8). As previously discussed (8), the explanation for the elevated plasma calcium concentration in uremic mice and dogs (30) remains enigmatic.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In a study by Bro et al, uremic apoE -/-mice that were fed a regular diet for 22 weeks had 50% higher total plasma cholesterol concentrations than normal apoE -/-mice (94). Plasma triglyceride concentrations did not differ between uremic and normal apoE -/-mice (94,95). This is in contrast to our trend of decreased cholesterol and triglycerides in CKD LDLr -/-mice when compared to CTL mice regardless of diet.…”
Section: Discussioncontrasting
confidence: 80%
“…Our model of CKD atherosclerosis is the first of its kind to demonstrate marked upregulation of mouse MPO and its specific oxidation products in response to reduced renal function and HFD in murine atherosclerosis. Similar to our work, apolipoprotein E deficient (apoE -/-) mice with chronic renal failure demonstrate enhanced atherosclerosis with increased macrophage infiltration and 3-nitrotyrosine expression in their atherosclerotic lesions, suggesting a similar process is plausible (81). However, this study did not specifically investigate if MPO or MPO-specific oxidation products are elevated.…”
Section: Discussionmentioning
confidence: 55%